The Civilizations of Asia and the Middle East - Krejci, Jaroslav. author. aut Link
XIV, 348 p.
Keywords: This book offers a comparative view of the world-views, values and institutions in Asia and the Middle East. The account takes the form of a historical narrative, focused on the most relevant events and features in the process of continual change.